2016
DOI: 10.5897/ajar2015.10404
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity assay of maize (Zea mays L.) inbreds based on morphometric traits and SSR markers

Abstract: Twenty maize genotypes (19 inbred lines and a commercial hybrid) were studied assessing the extent of genetic diversity for 21 qualitative and quantitative morpho-metric traits and 18 expressed sequence tags-simple sequence repeats (EST-SSR) markers. A wide range of variation was observed among the 20 maize genotypes for quantitative traits predominantly for plant height, ear height, days to tasseling, days to silking, and kernel yield per plant. Among the qualitative traits, green-glume base, green internode,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 19 publications
1
5
0
Order By: Relevance
“…It is a multifunctional plant with wide adaptability to various agro-climatic conditions. Maize is widely cultivated in most regions of the world, at altitudes of up to 3,000 m above sea level, owing to the highest grain production potential among cereals ( Chakraborty et al, 2012 ; Madhav et al, 2016 ; Sah et al, 2020 ). In many countries, maize is grown in areas with the annual rainfall levels of 300 to 500 mm, although that amount is below the critical level for good yields ( Monfreda et al, 2008 ; Hanjra and Qureshi, 2010 ).…”
Section: Introductionmentioning
confidence: 99%
“…It is a multifunctional plant with wide adaptability to various agro-climatic conditions. Maize is widely cultivated in most regions of the world, at altitudes of up to 3,000 m above sea level, owing to the highest grain production potential among cereals ( Chakraborty et al, 2012 ; Madhav et al, 2016 ; Sah et al, 2020 ). In many countries, maize is grown in areas with the annual rainfall levels of 300 to 500 mm, although that amount is below the critical level for good yields ( Monfreda et al, 2008 ; Hanjra and Qureshi, 2010 ).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Pandit et al (2016) obtained PIC values ranging between 0.00 and 0.87 with an average of 0.65 in a study that involved 20 maize genotypes and 18 EST-SSR primer pairs, while the PIC values obtained by Vivodík et al, (2021) in a study that involved 20 genotypes of old maize lines and 5 ScoT markers ranged from 0.652 to 0.816 with an average of 0.738. However, in another study by Kumari et al, (2018) that involved 8 maize genotypes and 22 SSR primers, including phi 034 which was also used in the present study, low values of PIC ranged from 0.195 to 0.367 with an average of 0.297 while GD varied from 0.219 to 0.484 with an average of 0.373.…”
Section: Genetic Diversity Analysis Of the Drought-tolerant Maize Gen...mentioning
confidence: 89%
“…Dendrogram is a good tool for showing the relationships between the genotypes in a genetic diversity study (Pandit et al, 2016). The dendrogram that was used to illustrate the genetic relationship that existed between the maize genotypes identified extensive diversity between the genotypes.…”
Section: Genetic Diversity Analysis Of the Drought-tolerant Maize Gen...mentioning
confidence: 99%
See 1 more Smart Citation
“…Almeida et al, (6) used SSR markers and reported low genetic diversity (0.22 to 0.33) in normal maize and sweet corn compared to the main populations of International Maize and Wheat Improvement Center (CIMMYT), which displayed genetic distances of 0.45 to 0.61 with SSR markers. Pandit et al, (29) evaluated 18 primer pairs that produced 92 different markers with polymorphism information content (PIC) value ranging from zero to 0.87; three different dendrograms based upon the dissimilarity coefficients were constructed. The information about genetic diversity of maize inbred lines revealed by genetic markers could be useful in planning strategies for future maize breeding programs.…”
mentioning
confidence: 99%